Analisis Pengendalian Kualitas Batako di CV. Berkah Pandaan dengan Menggunakan Metode FMEA (Failure Mode and Effect Analysist) - Kholifan Fani; Nuriyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Kholifan fani, Engineering Study Program, Yudharta Pasuruan University Pasuruan, 02 July 2024. Batake Quality Control Analysis, At CV. BERKAH PANDAAN Using the FMEA (Failure Mode and Effect Analysis ) Method. The aim of this research data is to determinan the process of controlling the quality of bricks at CV. Berkah Pandaan using the FMEA (Failure Mode and Effect Analysis) Method. The approaches used are SWOT and FMEA. Failure Mode and Effect Analysis is defined as a method used to identify the causes and consequences of a failure. SWOT is the systematic identification of various factors to formulate company strategy. This analysis is based on logic that can maximize strengths and opportunities, but simultaneously minimize weaknesses and threats. Based on result of this research, the causes of defects that occur at CV. Be identified. BERKAH PANDAAN is caused by two thigs, namely in terms of humans and machiens, form the human perspective it is mosly caused by a lack of work concentration so that the quality of work decreases, this is triggered by working environmental conditions that are less supportive, including room temperatures that are too hot, insufficient lighting. Engine noise that is too loud in terms of the engine usually occurs because the engine is experiencing downtime.